2015
DOI: 10.1016/j.lungcan.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Final results from a Phase II study of pemetrexed and cisplatin with concurrent thoracic radiation after Pem-Cis induction in patients with unresectable locally advanced non-squamous non-small cell lung cancer (NSCLC)

Abstract: In this study of Pem-Cis induction CT followed by full-dose Pem-Cis with concurrent RT, median PFS was 10.6 months and toxicity was manageable, in line with previous data on Pem-Cis plus RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…These data align with results from the overall study population,3 suggesting that this regimen is feasible in elderly and non-elderly patients alike and may help in making the disease surgically resectable in elderly patients with good performance. Findings should be interpreted with caution due to the exploratory nature and small number of elderly patients included.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…These data align with results from the overall study population,3 suggesting that this regimen is feasible in elderly and non-elderly patients alike and may help in making the disease surgically resectable in elderly patients with good performance. Findings should be interpreted with caution due to the exploratory nature and small number of elderly patients included.…”
supporting
confidence: 83%
“…In a phase II study, treatment with two cycles of pemetrexed-cisplatin (Pem-Cis) induction, followed by full-dose Pem-Cis plus concurrent RT was well tolerated and effective in 90 patients with stage IIIA/IIIB unresectable, non-squamous NSCLC 3. Here, we report by-age subgroup data for 17 elderly (aged >70 years) and 73 non-elderly patients (aged ≤70 years).…”
mentioning
confidence: 97%
“…Cisplatin is the first drug approved for clinical use for cancer chemotherapy [22]. It has become evident that cisplatin-based chemotherapy could improve the prognosis of patients and prolong survival of patients with various cancer types including non-small cell lung cancer [23, 24]. Currently, cisplatin-based chemotherapy is an accepted standard of care for systemic therapy for patients at advanced stages of NSCLC [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…A phase I study of pemetrexed plus cisplatin followed by pemetrexed consolidation therapy with dose-escalation of TRT in patients with locally advanced nonsquamous NSCLC showed that the objective response rate was 83 %. A phase II study of pemetrexed plus cisplatin with concurrent TRT in Stage IIIA or Stage IIIB non-squamous NSCLC showed a best overall response of 72 %(PFS, 13.8 months; OS, 26.2 months) [ 43 ]. Furthermore, a randomized phase III study was performed to investigate the effect of pemetrexed 500 mg/m 2 + cisplatin 75 mg/m 2 or etoposide 50 mg/m 2 + cisplatin 50 mg/m 2 with plus concurrent TRT followed by pemetrexed consolidation cytotoxic chemotherapy in locally advanced nonsquamous NSCLC [ 44 ].…”
Section: Discussionmentioning
confidence: 99%